Contriving Dye by Outcrossing AI6061/SiC/Red Mud Composites - Mrs. K. S. Thivya, Mrs. Gomathi Nagajothi, Mrs. K. Jayabharathi, Mrs. S. Elakkiya (International Journal of Control and Automation, 2020)
The research in waste management is going viral throughout the Universe. Many researchers are coming with many reliable results that can be employed in many fields like construction, manufacturing, pharmaceuticals, etc. One such interesting factor that attracts the researchers all over the world is Aluminium based metal matrix composites. This can be employed in the construction field by fabricating dye with proper compositions of different elements and ratios, which is discussed in detail in this paper. Among Aluminium alloys Al6061 is widely used for engineering applications including automobile, aerospace, marine and structural applications where superior mechanical effects such as durability, firmness, etc are required. Al6061 has superior corrosion resistance and it is suitable for marine structural applications. It is the lightweight material, cost-effective and high-performance material, so it is preferable for structural and non-structural applications. SiC is the most used as the reinforcing material with Al6061. Because when SiC reinforcing with Al6061 the wear resistance is improved. The fabrication of the Metal Matrix Composite, Powder Metallurgy technique, suitable die design specification, and material is proposed.